2000
DOI: 10.1083/jcb.150.6.1385
|View full text |Cite
|
Sign up to set email alerts
|

Absence of α-Syntrophin Leads to Structurally Aberrant Neuromuscular Synapses Deficient in Utrophin

Abstract: The syntrophins are a family of structurally related proteins that contain multiple protein interaction motifs. Syntrophins associate directly with dystrophin, the product of the Duchenne muscular dystrophy locus, and its homologues. We have generated α-syntrophin null mice by targeted gene disruption to test the function of this association. The α-Syn−/− mice show no evidence of myopathy, despite reduced levels of α-dystrobrevin–2. Neuronal nitric oxide synthase, a component of the dystrophin protein complex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
230
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 212 publications
(242 citation statements)
references
References 59 publications
(99 reference statements)
10
230
0
Order By: Relevance
“…The ␣-Syn Ϫ/Ϫ mice used in this study have a relatively subtle structural defect; ␣-syntrophin is missing, but the other four syntrophin isoforms are still expressed (6). Moreover, the basic structure of the dystrophin-associated protein complex remains intact in ␣-Syn Ϫ/Ϫ mice, and only the population of AQP4 in perivascular astroglial end-feet is mislocalized (4).…”
Section: Discussionmentioning
confidence: 99%
“…The ␣-Syn Ϫ/Ϫ mice used in this study have a relatively subtle structural defect; ␣-syntrophin is missing, but the other four syntrophin isoforms are still expressed (6). Moreover, the basic structure of the dystrophin-associated protein complex remains intact in ␣-Syn Ϫ/Ϫ mice, and only the population of AQP4 in perivascular astroglial end-feet is mislocalized (4).…”
Section: Discussionmentioning
confidence: 99%
“…In that case ∼50% central nuclei are observed, but little mononuclear infiltration was seen and the overall dystrophy is considerably less severe than in mdx. α-Syntrophin knockout mice show decreased sarcolemmal expression of α-dystrobrevin-2 and nNOS, but no myopathic symptoms (27); (28). Finally, α-dystrobrevin-1 has been shown to bind to the intermediate filament proteins desmuslin and syncoilin [Newey, 2001;Blake, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…Hindlimb suspension (unloading) causes muscle atrophy, delocalization, and posttranscriptional downregulation of nNOSμ protein to approximately 50% of wild-type levels (Tidball et al 1998;Suzuki et al 2007). Full nNOSμ expression requires its localization at the sarcolemma (Adams et al 2000). Suzuki et al (2007) reported that cytosolic nNOS activity is increased by unknown mechanisms and promotes hindlimb muscle atrophy through the activation of the forkhead transcription factor FoxO3 pathway (Figure 1).…”
Section: Inactivity-dependent Regulation Of Nnos Expression and Catalmentioning
confidence: 99%
“…Skeletal muscles express two alternatively spliced nNOS isoforms, nNOSμ and nNOSβ, both of which are expressed in fast and slow muscle types (Silvagno et al 1996;Stamler and Meissner 2001;Percival et al 2010, Figure 1). nNOSμ is scaffolded to the subsarcolemmal dystrophin glycoprotein complex (DGC) and neuromuscular junction (Brenman et al 1995(Brenman et al , 1996Adams et al 2000). The sarcolemmal nNOSμ association requires α-syntrophin, dystrophin, and α-dystrobrevin (Brenman et al 1995(Brenman et al , 1996Grady et al 2000;Adams et al 2000Adams et al , 2008.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation